2002
DOI: 10.1161/01.cir.0000023921.93743.89
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Integrity and Function in Atherogenesis

Abstract: Background-Coronary atherosclerotic disease remains the leading cause of death in the Western world. Although the exact sequence of events in this process is controversial, reactive oxygen and nitrogen species (RS) likely play an important role in vascular cell dysfunction and atherogenesis. Oxidative damage to the mitochondrial genome with resultant mitochondrial dysfunction is an important consequence of increased intracellular RS. Methods and Results-We examined the contribution of mitochondrial oxidant gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
318
2
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(344 citation statements)
references
References 36 publications
18
318
2
5
Order By: Relevance
“…2,16 Recent studies have indicated that mtDNA damage affects mitochondrial function and thus plays an important role in the pathophysiology of various cardiovascular diseases, such as heart failure 17 and atherosclerosis. 18 This vicious circle may result in myocardial functional and structural damage in heart failure. The equivalent results observed between in vivo and in vitro indicate that TNF-␣ plays an important role in oxidative stress in the pathogenesis of myocardial remodeling and failure.…”
Section: Discussionmentioning
confidence: 99%
“…2,16 Recent studies have indicated that mtDNA damage affects mitochondrial function and thus plays an important role in the pathophysiology of various cardiovascular diseases, such as heart failure 17 and atherosclerosis. 18 This vicious circle may result in myocardial functional and structural damage in heart failure. The equivalent results observed between in vivo and in vitro indicate that TNF-␣ plays an important role in oxidative stress in the pathogenesis of myocardial remodeling and failure.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial-derived oxidative stress has also been implicated in chronic inflammation, cancer progression (206), diabetes mellitus (148,152,(317)(318)(319)378), and atherosclerosis (21,258). Mitochondrial-derived ROS (MtROS) also contributes to LPS-mediated production of pro-inflammatory cytokines IL-1b, IL-6, and TNF-a (48).…”
Section: B Mitochondrial-derived Ros In Inflammationmentioning
confidence: 99%
“…Thus, the response to CEM exposure involved changes that take place at the cell membrane (e.g., response to extracellular signals, ion transport, cell adhesion). DISCUSSION Cardiac disease leads to impairment of energy supply through mitochondria damage (Ballinger, 2005;Ballinger et al, 2002;Bulteau et al, 2005;Kang and Hamasaki, 2005;Rosenberg, 2004). Thus, in the CEM rat model of heart toxicity, where mitochondria damage occurs, we explored changes in heart transcripts associated with energy supply and demand, and how changes in heart transcripts may help to maintain heart function.…”
Section: Histopathologymentioning
confidence: 99%